(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Stakeholders often face many problems related to financial information in corporate financial reports in terms of transparency and the ability to interpret the numbers contained in them. Likewise, the potential risks related to the terms mentioned therein. However, the (XBRL) provides an interactive environment for the beneficiaries of the financial reports. The research discusses the contribution, of the language of extended business reports, in providing information and data that helps stakeholders in making decisions. in a way that enhances transparency in companies ’business and comparability between them. XBRL relies on providing an integrated services model for management, full supervision of operations, and improving the quality of financial reports on financial activities. It is also assumed that the use of XBRL will provide stakeholders and recipients of the financial statements with financial information about the companies that are credible. XBRL can help create a type of data comparison more quickly and at a lower cost. In addition, XBRL facilitates reporting for internal users as well as external users. As a result, XBRL is able to meet the expectations of beneficiaries, regardless of the type of data they wish to obtain.